Museums, communication and young people: the communication and its effects in the population of reference of the museum - Becerra Muñoz, Elena; Domínguez Contreras, Beatriz (Historia y Comunicación Social, 2014)
The heritage leads us directly to the museums as “physical support” that allow us to collect, catagorize, organize and even decorate part of the cultural and artistic heritage of a city. You need to share the art with the citizen (tourist or local), so that in this relationship, the art will become something that is alive, and something that will progress and exceed the era in which the artwork was created. This temporary fusion - when the past merges with the present - also includes a cultural exchange between the creation and the one who contemplates it. This cultural exchange inspires a new work, a work which will not always have an external physical expression, but one that can modulate our lives and inspire the art of the future. “The legacy has grown from the inherited artistic treasure of our ancestors, that we need to transmit to future generations, the attitude and action of contemporary society that elects and adapted elements of their past and their present, giving them a significant value as an expression of their identity.” Identity, therefore, shown in art (tells us as we were, how we are, how we could be...) that links, necessarily, heritage and citizenship. At this point we ask ourselves the following question: is the citizen aware of the art in his/her city? The tendency to become connoisseurs of Museums only as a tourist in a far away city is too common. One must revive their interest in investigating the field closest to the individual. The words of Morente del Monte (2007: 18) guide us toward consideration of heritage as something alive that merges with the society, and with its citizens. And it is through this heritage, we know the history and the culture, a culture that nourishes and configures our identity. Yesterday largely conditions today as an indissoluble relationship between culture and identity.
Keywords: Culture; Communication; Identity; young people and museums; cultural supply.